Tramas e dramas da sucessão na agricultura familiar: percepção dos jovens no território Centro-Sul do Paraná - Tabarro, Cristiane (2018)
This research presents a look at plots and dramas that intertwined the rural youth of the territory south of Paraná, having focus on the municipality of Guamiranga, with connections to the actors of the territory and their relationships before the generational succession in family agriculture and retention of young people in rural areas. The study is a qualitative research, with subjective analysis, through documentary analysis method of interpretation of Karl Mannheim, to describe and understand the individual entities. That it gives a more complex analysis, systemic, critical and subjective processes established relations in line with the diversification of areas cultivated with tobacco. The research also brings to the analysis the act to understand development as art - in which demonstrate the quantify and qualify. The information has been collected, tabulated and compared in its two aspects, directing theresult from the above presented. The study shows the different perceptions of the young people and their parents in relation to the theme, the advances and setbacks in the speeches and actions inrelation to the rural environment to be a space of opportunity that "hosts" and/or "expelled" the young, as well as the battles faced in this scenario here characterized as dramas and plots. The survey shows the importance of territorial dialogue relations for effective policy action where young people and their families act, through their networks and concrete actions around the common goal of strengthening family agriculture and thewhole plot in which it is inserted.